2018
DOI: 10.1093/cvr/cvy135
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of endothelial CXCL16/CXCR6-platelet–leucocyte axis in angiotensin II-associated metabolic disorders

Abstract: CXCR6 expression on platelet-bound monocytes and CD8+ lymphocytes may constitute a new membrane-associated biomarker for adverse cardiovascular events. Moreover, pharmacological modulation of this axis may positively affect cardiovascular outcome in metabolic disorders linked to Ang-II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 41 publications
4
21
0
1
Order By: Relevance
“…Using PFA‐100, we found that the PFA‐100 CT of MetS patients was significantly shorter than that of the NC group (106 s vs 111 s, P < .05). This result provides evidence of platelet hyperactivation in MetS, similarly to previous studies 8‐11 . As we know, platelet activation is known to be associated with atherogenesis and cardiovascular morbidity 21 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Using PFA‐100, we found that the PFA‐100 CT of MetS patients was significantly shorter than that of the NC group (106 s vs 111 s, P < .05). This result provides evidence of platelet hyperactivation in MetS, similarly to previous studies 8‐11 . As we know, platelet activation is known to be associated with atherogenesis and cardiovascular morbidity 21 .…”
Section: Discussionsupporting
confidence: 88%
“…Platelet activation has previously been reported in MetS 8‐11 . However, as far as we know, there are few studies evaluating platelet function in MetS subjects.…”
Section: Introductionmentioning
confidence: 93%
“…CXCL16 is the only ligand for the CXCR6 receptor. The CXCR6/CXCL16 axis has a rather bad press as its increased activity was shown to be associated with invasion of some cancers [38] and development of cardiometabolic disorders [39]. However, on the other hand, CXCL16 was demonstrated to be a critical mediator of muscle regeneration, which suppresses the development of fibrosis [40].…”
Section: Discussionmentioning
confidence: 99%
“…ARB treatment reduced the effects of CXCL1 and CXCL2 upregulation and increased oxidative stress [ [118] , [119] , [120] ]. CXCL16 is involved in Angiotensin II associated metabolic disorders and atherosclerosis, and its secretion is blocked by ARBs [ 121 , 122 ]. ARB treatment reduces MCP-1 upregulation during lung injury, inhibits monocyte recruitment and reduces lung fibrosis development [ 123 , 124 ].…”
Section: Discussionmentioning
confidence: 99%